The Sacred Coexistence: Wild Animals in the Peasant Homestead - Vaitkevičienė, Daiva (Tautosakos darbai, 2018)
The subject of the article are the grounds of the harmonious relationship between humans and the wild animals living in the traditional Lithuanian peasant homestead. As a point of departure, the author chooses the question from the sphere of deep ecology: on what cultural and worldview grounds do humans construct their connections with other living beings? Although the notion of coexistence comes from the natural sciences and defines relations between different species in the same ecological system, this article deals with coexistence as a phenomenon primarily conditioned by culture – i. e., by the human view of the animals and attitude towards them. The author analyzes folk narratives and popular beliefs in order to establish the character of relationship between humans and four kinds of animals living in the homestead – namely, the grass snake (Natrix natrix), the weasel (Mustela nivalis), the white stork (Ciconia ciconia), and the swallow (Hirundo rustica). In the first part, the author investigates the natural and economical prerequisites for the ecological coexistence of these animals and humans. Having paid much attention to the development of agriculture and formation of the agrarian landscape, she explains timing and causes for the wild animals to settle in the Lithuanian peasant homesteads. The second part of the article reveals the religious causes that lead humans to keep the suitable living conditions for the animals in question, not only protecting and safeguarding them, but also considering them sacred. Until the middle of the 20th century, Lithuanians regarded the grass snake, the weasel, the stork and the swallow to be the guardians of the home, ensuring good fortune with livestock and plentiful harvests. Besides, images of these animals became part of the concept of the soul, finding their way into the stories of birth, death, and afterlife. The grass snake (as perhaps also the weasel) had connections with the souls of the ancestors, while the swallow and particularly the stork were in charge of the reincarnation, since these birds allegedly were able to transport the souls back from the celestial afterworld. The coexistence of humans and animals in the homestead not only joins the different kinds of life and their mythical meanings, but also incorporates deities into this system. The birds embody the atmospheric forces governed by the Thunderer, while the grass snake and weasel are manifestations of the sacred earth. Therefore, we can define the harmonious coexistence of humans and animals in the homestead as sacred.